High-Risk Neuroblastoma Treatment Review - Valeria Smith; Jennifer Foster (MDPI AG, 2018)
Neuroblastoma is the most common extracranial solid tumor in children. One subset, high-risk neuroblastoma, is very difficult to treat and requires multi-modal therapy. Intensification of therapy has vastly improved survival rates, and research is focused on novel treatments to further improve survival rates. The current treatment schema is divided into three stages—induction, consolidation, and maintenance. This review serves as an overview of the current treatment for high-risk neuroblastoma and a glimpse at current research for future therapy.